Manufacturing method of brazing sheet
By manufacturing welding materials of sandwich structures under an inert atmosphere and using rare earth metal elements to destroy the oxide film, the problems of degradation of flux-free welding quality and high equipment cost are solved, and efficient and low-cost welding effect is achieved.
Patent Information
- Application Number
- JP2020160434
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-09-25
- Publication Date
- 2025-01-30
- Estimated Expiration
- 2040-09-25
AI Technical Summary
In the prior art In flux-free welding method, welding quality is prone to decline and equipment and maintenance costs are high, and metal elements are prone to oxidation during welding, resulting in the formation of oxide films and affecting the welding effect.
Welding methods manufactured under an inert atmosphere are adopted to form welding materials with sandwich structures through hot rolling and cold rolling processes, and rare earth metal elements such as magnesium and lithium are used to destroy the oxide film during the welding process, avoiding the use of flux.
High-quality flux-free welding is achieved, which reduces equipment and maintenance costs, and effectively destroys the oxide film through rare earth metal elements, improving the welding effect.
Smart Images

Figure 0007624300000003 
Figure 0007624300000001 
Figure 0007624300000002
Abstract
Description
[Technical Field]
[0001] The present invention relates to a method for manufacturing a brazing sheet. [Background technology]
[0002] Aluminum products such as heat exchangers and machine parts have many parts made of aluminum material (including aluminum and aluminum alloys; the same applies below). These parts are often brazed using a brazing sheet that has a core material and a brazing filler metal applied to at least one side of the core material. The core material of the brazing sheet is generally made of an aluminum alloy with a solidus temperature of 620°C or higher. The brazing filler metal is made of an Al-Si (aluminum-silicon) alloy with a solidus temperature of approximately 577°C.
[0003] A commonly used brazing method for aluminum materials is the flux brazing method, in which flux is applied to the surfaces of the parts to be joined, i.e., the parts to be joined by brazing, before brazing. However, when brazing is performed using the flux brazing method, the flux and its residue adhere to the surface of the aluminum product after brazing is completed. Depending on the application of the aluminum product, this flux and its residue may cause problems. Furthermore, pickling treatment is required to remove the flux and its residue, and in recent years, the cost burden of this treatment has become a problem.
[0004] To avoid the problems associated with the use of flux, some aluminum products employ the so-called vacuum brazing method, in which brazing is performed in a vacuum without applying flux to the surface of the parts to be joined. However, vacuum brazing has problems such as lower productivity than flux brazing and a tendency for the quality of the brazed joint to deteriorate. Furthermore, the brazing furnaces used in vacuum brazing have higher equipment and maintenance costs than conventional brazing furnaces.
[0005] Therefore, a so-called flux-free brazing method has been proposed, in which brazing is performed in an inert gas atmosphere without applying flux to the surface of the parts to be joined. The core material of the brazing sheet and the brazing filler metal used in the flux-free brazing method contain metal elements such as Mg (magnesium) that are more easily oxidized than Al (aluminum). These metal elements have the effect of destroying the oxide film that exists on the surface of the brazing sheet and on the surface of the mating material to be joined to the brazing sheet during brazing. In flux-free brazing, brazing is performed by utilizing the action of these metal elements.
[0006] Patent Document 1 also describes a method for producing an aluminum brazing sheet clad with an Al-Si-Mg (aluminum-silicon-magnesium) alloy as a brazing material, in which the surface is treated with an alkaline solution at a rate of 0.02 to 5 g / m 2 A method for producing a brazing sheet for vacuum brazing has been proposed, which is characterized by etching and then neutralizing the sheet. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP-A-4-100696 Summary of the Invention [Problem to be solved by the invention]
[0008] However, when brazing is performed by a flux-free brazing method using a brazing sheet obtained by the manufacturing method described in Patent Document 1, there is a problem in that brazing defects are likely to occur.
[0009] The present invention has been made in view of the above background, and aims to provide a method for manufacturing a brazing sheet that can provide a brazing sheet with excellent brazing properties in flux-free brazing. [Means for solving the problem]
[0010] One aspect of the present invention is a method for manufacturing a brazing sheet for brazing aluminum materials in an inert gas atmosphere without using a flux, The aluminum alloy sheet is made by stacking a plurality of aluminum ingots, the aluminum ingots including a core ingot made of an aluminum material and a brazing filler ingot made of an Al-Si alloy and disposed on at least one surface of the core ingot, and among the plurality of aluminum ingots, the core material ingot, the brazing material ingot, and A block for core material and a block for brazing material were disposed between the block for core material and the block for brazing material. Of aluminum ingots a lamination step for producing a clad block in which at least one aluminum block contains a metal element that is more easily oxidized than Al; a hot rolling process for producing a clad plate including a core material made of the core ingot and a brazing material made of the brazing material ingot and disposed on at least one surface of the core ingot by hot rolling the clad ingot; a cold rolling step of subjecting the clad plate to one or more passes of cold rolling; Between passes of cold rolling in the cold rolling step or after completion of the cold rolling step, the concentration of NaOH is 0.05 mass% or more and 1.0 mass% or less. The concentration of KOH is 0.10 mass % or more and 1.0 mass % or less. and an etching step of etching the surface of the clad plate using an alkaline etching solution. [Effects of the Invention]
[0011] In the brazing sheet manufacturing method, the clad ingot is hot-rolled and cold-rolled to produce a clad plate. A brazing filler metal made of an Al-Si alloy is disposed on at least one side of the clad plate. The surface of the clad plate is etched using the specific alkaline etching solution, thereby removing the strong oxide film formed on the surface of the clad plate during the manufacturing process. Therefore, the brazing sheet obtained by the manufacturing method has portions on its surface that have a thinner and more fragile oxide film than the oxide film formed during the manufacturing process of the brazing sheet.
[0012] Furthermore, the brazing sheet obtained by the above-described manufacturing method contains a metal element that is more easily oxidized than Al in at least one layer between the core material and the brazing filler metal among the multiple layers that make up the brazing sheet. Therefore, during brazing, the weak portions of the oxide film on the brazing sheet are easily weakened or destroyed by the metal element, allowing brazing to be performed without the use of flux. Therefore, the brazing sheet obtained by the above-described manufacturing method can improve brazeability in flux-free brazing.
[0013] As described above, according to the above-described embodiment, it is possible to provide a method for manufacturing a brazing sheet that can obtain a brazing sheet that has excellent brazing properties in flux-free brazing. [Brief explanation of the drawings]
[0014] [Figure 1] FIG. 1 is a side view of a test specimen used in a gap filling test in the examples. DETAILED DESCRIPTION OF THE INVENTION
[0015] <Lamination process> In the method for manufacturing the brazing sheet, first, a plurality of aluminum ingots are prepared, including a core ingot that will ultimately become the core of the brazing sheet and a brazing filler ingot that will ultimately become the brazing filler of the brazing sheet. These aluminum ingots are then stacked in a desired order to form a clad ingot, in a lamination process. The stacking order and number of layers of the aluminum ingots in the clad ingot can be appropriately determined depending on the desired layer structure and number of layers of the brazing sheet.
[0016] For example, to obtain a brazing sheet with a two-layer structure comprising a core material and a brazing filler metal layered on one side of the core material, the clad ingot can be composed of two aluminum ingots: a core material ingot and a brazing filler metal layered on one side of the core material ingot. Similarly, to obtain a brazing sheet with a three-layer structure comprising a core material and a brazing filler metal layered on both sides of the core material, the clad ingot can be composed of three aluminum ingots: a core material ingot and a brazing filler metal layered on both sides of the core material ingot.
[0017] Furthermore, when preparing an aluminum ingot, an aluminum ingot having a different chemical composition from the core ingot and the brazing filler ingot can be prepared, and this aluminum ingot can be layered on the core ingot and the brazing filler ingot to form a clad ingot, thereby obtaining a brazing sheet with layers different from the core and brazing filler ingots. For example, when preparing an aluminum ingot, an intermediate ingot having a different chemical composition from the core ingot and the brazing filler ingot can be prepared, and the core ingot, intermediate ingot, and brazing filler ingot can be layered in this order to form a clad ingot, thereby ultimately obtaining a brazing sheet with an intermediate material made of the intermediate ingot between the core and the brazing filler ingot. When preparing an aluminum ingot, an aluminum ingot having a different chemical composition from the core ingot can be prepared, and the clad ingot can be layered in this order to form a brazing sheet with a brazing filler ingot layered on one side of the core material and a cladding material made of the cladding ingot.
[0018] Among the multiple aluminum blocks constituting the clad block, Core blocks, brazing blocks, and At least one aluminum block disposed between the core block and the brazing block contains a metal element that is more easily oxidized than Al (aluminum). Examples of metal elements that are more easily oxidized than Al include Mg (magnesium), Li (lithium), and Ca (calcium). These metal elements can destroy oxide films present on the surfaces of the brazing sheet and the mating material during brazing. Therefore, the brazing sheet obtained by the above-described manufacturing method enables flux-free brazing.
[0019] The metal elements described above may be contained, for example, in the core ingot or in the brazing filler ingot. Furthermore, the metal elements described above may be contained in both the core ingot and the brazing filler ingot. When an intermediate ingot is placed between the core ingot and the brazing filler ingot, the metal elements described above can also be added to the intermediate ingot. By subjecting the clad ingot thus constructed to hot rolling and cold rolling, a brazing sheet can be obtained in which a metal element that is more easily oxidized than Al is contained in at least one layer between the core ingot and the brazing filler ingot, and which is applicable to flux-free brazing.
[0020] From the viewpoint of further improving brazing performance in flux-free brazing, the clad ingot preferably contains at least one of Mg and Li, more preferably Mg, as a metal element that is more easily oxidized than Al. From the same viewpoint, it is also preferable that at least one of the brazing filler metal ingot and the aluminum ingot adjacent to the brazing filler metal ingot contains a metal element that is more easily oxidized than Al.
[0021] The detailed structure of each aluminum block contained in the clad block will be described below.
[0022] (Lump for heartwood) The core ingot is an aluminum ingot that will become the core of the brazing sheet after the clad ingot is hot-rolled and cold-rolled. The aluminum material constituting the core ingot can be an aluminum material with a higher solidus temperature than the Al-Si alloy constituting the brazing filler ingot. The core ingot may be made of, for example, JIS A1000 series aluminum, A3000 series alloy, A5000 series alloy, or A6000 series alloy.
[0023] More specifically, the aluminum material constituting the core ingot may have a chemical composition consisting of Al and unavoidable impurities.Furthermore, the aluminum material constituting the core ingot may contain, in addition to Al and unavoidable impurities, one or more alloying elements selected from the group consisting of Fe (iron), Si (silicon), Mg (magnesium), Cu (copper), Mn (manganese), Zn (zinc), Cr (chromium), Ti (titanium), Zr (zirconium), Sn (tin), and In (indium).
[0024] When a brazing sheet is to be obtained in which the core material contains metal elements that are more easily oxidized than Al, the core ingot may be made of an aluminum material containing more than 0% by mass and not more than 3.0% by mass of Mg. The chemical composition of the core material in the brazing sheet is the same as that of the core ingot. The range of the alloy element content that can be contained in the core ingot and the reasons for this limitation are explained in detail below.
[0025] ·Fe: 0 mass% or more and 1.5 mass% or less The aluminum material constituting the core ingot may contain 1.5 mass% or less of Fe as an optional component. When the core ingot contains more than 0 mass% and 1.5 mass% or less of Fe, a brazing sheet with a core material containing Fe can be obtained. The Fe in the core material has the effect of improving the strength of the core material.
[0026] However, if the Fe content in the core material is excessively high, the corrosion resistance of the core material may deteriorate. Furthermore, in this case, large precipitates may easily form in the core material, which may result in a decrease in the formability of the brazing sheet. By producing a brazing sheet using a core ingot containing more than 0% by mass and not more than 1.5% by mass of Fe, these problems can be avoided while further improving the strength of the core material.
[0027] ·Si: 0 mass% or more and 1.5 mass% or less The aluminum material constituting the core ingot may contain up to 1.5% by mass of Si as an optional component. When the core ingot contains more than 0% by mass and up to 1.5% by mass of Si, a brazing sheet with a core material containing Si can be obtained. The Si in the core material has the effect of improving the strength of the core material.
[0028] However, if the Si content in the core material is excessively high, the melting point of the core material will decrease, which may lead to a deterioration in brazability. By producing a brazing sheet using a core ingot containing more than 0% by mass and not more than 1.5% by mass of Si, it is possible to further improve the strength of the core material while avoiding a deterioration in brazability.
[0029] ·Mg: 0 mass% or more and 3.0 mass% or less The aluminum material constituting the core ingot may contain 3.0% by mass or less of magnesium as an optional component. When the core ingot contains more than 0% by mass and 3.0% by mass or less of magnesium, a brazing sheet with a core material containing magnesium can be obtained. The magnesium in the core material diffuses and migrates to the brazing filler metal due to heating during brazing. The magnesium that migrates to the brazing filler metal then destroys the oxide film present on the surface of the brazing sheet and the surface of the mating material, enabling flux-free brazing.
[0030] To further improve brazing performance in flux-free brazing, the Mg content in the core ingot is preferably 0.10% by mass or more, more preferably 0.20% by mass or more, which allows a larger amount of Mg to migrate from the core to the brazing filler metal due to heating during brazing.
[0031] On the other hand, if the Mg content in the core ingot is excessively high, a large amount of Mg is likely to reach the surface of the brazing sheet during brazing. If the Mg that reaches the surface of the brazing sheet is oxidized during brazing, this may lead to a deterioration in brazability. By setting the Mg content in the core ingot to 3.0 mass% or less, preferably 1.5 mass% or less, the amount of Mg oxides generated during brazing can be further reduced, thereby preventing a deterioration in brazability.
[0032] ·Cu: 0 mass% or more and 2.0 mass% or less The aluminum material constituting the core ingot may contain 2.0 mass% or less of Cu as an optional component. When the core ingot contains more than 0 mass% and 2.0 mass% or less of Cu, a brazing sheet with a core material containing Cu can be obtained. Cu in the core material has the effect of improving the strength of the core material. Cu also has the effect of adjusting the potential of the core material and improving corrosion resistance.
[0033] However, if the Cu content in the core material is excessively high, intergranular corrosion is likely to occur. Furthermore, in this case, the melting point of the core material decreases, which may lead to a deterioration in brazability. By producing a brazing sheet using a core ingot containing more than 0% by mass and not more than 2.0% by mass of Cu, these problems can be avoided while further improving the strength and corrosion resistance of the core material.
[0034] ·Mn: 0 mass% or more and 2.0 mass% or less The aluminum material constituting the core ingot may contain 2.0 mass% or less of Mn as an optional component. When the core ingot contains more than 0 mass% and 2.0 mass% or less of Mn, a brazing sheet with a core material containing Mn can be obtained. Mn in the core material has the effect of improving the strength of the core material. Mn also has the effect of adjusting the potential of the core material and improving corrosion resistance.
[0035] However, if the Mn content in the core ingot is excessively high, cracks are more likely to occur in the core during the manufacturing process of the brazing sheet. By producing a brazing sheet using a core ingot containing more than 0 mass% and not more than 2.0 mass% Mn, it is possible to further improve the strength and corrosion resistance of the core while avoiding deterioration in the manufacturability of the brazing sheet.
[0036] ·Zn: 0 mass% or more and 6.5 mass% or less, Sn: 0 mass% or more and 0.10 mass% or less, In: 0 mass% or more and 0.10 mass% or less The aluminum material constituting the core ingot may optionally contain one or more of the following elements: 6.5% by mass or less Zn, 0.10% by mass or less Sn, and 0.10% by mass or less In. When the core ingot contains one or more of the following elements: more than 0% by mass and 6.5% by mass or less Zn, more than 0% by mass and 0.10% by mass or less Sn, and more than 0% by mass and 0.10% by mass or less In, a brazing sheet can be obtained that includes a core material containing these elements.
[0037] Zn, Sn, and In in the core material have the effect of making the natural electrode potential of the core material less noble. By making the natural electrode potential of the core material less noble, the core material can function as a sacrificial anode in the brazed aluminum product. However, if the Zn, Sn, or In content in the core material is excessively high, the natural electrode potential of the core material will be excessively reduced, and the sacrificial corrosion protection effect may be prematurely impaired. By producing a brazing sheet using a core material ingot containing one or more elements selected from the group consisting of more than 0% by mass and not more than 6.5% by mass of Zn, more than 0% by mass and not more than 0.10% by mass of Sn, and more than 0% by mass and not more than 0.10% by mass of In, the core material can function as a sacrificial anode and maintain the sacrificial corrosion protection effect of the core material for a longer period of time.
[0038] ·Cr: 0 mass% or more and 0.30 mass% or less, Zr: 0 mass% or more and 0.30 mass% or less The aluminum material constituting the core ingot may optionally contain one or two of 0.30% by mass or less of Cr and 0.30% by mass or less of Zr. When the core ingot contains one or two of the elements Cr: more than 0% by mass and 0.30% by mass or less and Zr: more than 0% by mass and 0.30% by mass or less, a brazing sheet can be obtained that includes a core material containing these elements.
[0039] Cr and Zr have the effect of increasing the crystal grain size of the core material and suppressing the occurrence of erosion. However, if the Cr or Zr content in the core ingot is excessively high, cracks are more likely to occur in the core material during the brazing sheet manufacturing process. By producing a brazing sheet using a core ingot containing one or two elements of more than 0% by mass and not more than 0.30% by mass of Cr and more than 0% by mass and not more than 0.30% by mass of Zr, it is possible to more effectively suppress the occurrence of erosion while avoiding deterioration in the manufacturability of the brazing sheet.
[0040] ·Ti: 0 mass% or more and 0.30 mass% or less The aluminum material constituting the core ingot may contain up to 0.30% by mass of Ti as an optional component. When the core ingot contains more than 0% by mass and up to 0.30% by mass of Ti, a brazing sheet with a core material containing Ti can be obtained. The Ti in the core material causes corrosion of the core material to progress in layers, inhibiting the progression of corrosion in the depth direction.
[0041] However, if the Ti content in the core ingot is excessively high, large precipitates are likely to form in the core ingot, which may lead to deterioration of rolling properties during hot rolling and cold rolling. This may also lead to deterioration of the corrosion resistance of the core. By producing a brazing sheet using an intermediate ingot containing more than 0% by mass and up to 0.30% by mass of Ti, these problems can be avoided while more effectively suppressing the progression of corrosion in the depth direction of the core.
[0042] From the viewpoint of obtaining the above-mentioned effects in a balanced manner, the aluminum material constituting the core ingot contains Fe: 0.05% by mass or more and 0.50% by mass or less, Si: 0.10% by mass or more and 0.50% by mass or less, Mg: 0.10% by mass or more and 1.0% by mass or less, Cu: 0.05% by mass or more and 0.50% by mass or less, Mn: 0.50% by mass or more and 1.5% by mass or less, and Ti: 0.01% by mass or more and 0.15% by mass or less, with the remainder being Al and unavoidable impurities. It is preferable that the alloy has a chemical composition consisting of Fe: 0.05% by mass to 0.30% by mass, Si: 0.15% by mass to 0.35% by mass, Mg: 0.30% by mass to 1.0% by mass, Cu: 0.10% by mass to 0.50% by mass, Mn: 1.0% by mass to 1.3% by mass, and Ti: 0.01% by mass to 0.15% by mass, with the balance being Al and unavoidable impurities.
[0043] Furthermore, when attempting to obtain a brazing sheet that does not contain Mg in the core material, it is preferable that the aluminum material constituting the core ingot contains Fe: 0.05% by mass or more and 0.30% by mass or less, Si: 0.15% by mass or more and 0.35% by mass or less, Cu: 0.10% by mass or more and 0.50% by mass or less, Mn: 1.0% by mass or more and 1.3% by mass or less, and Ti: 0.01% by mass or more and 0.15% by mass or less, with the remainder being Al and unavoidable impurities.
[0044] (Brazing material block) The brazing filler metal ingot is an aluminum ingot that becomes the brazing filler metal for the brazing sheet after hot rolling and cold rolling of the clad ingot. The aluminum material constituting the brazing filler metal ingot can be an Al-Si alloy, which is an aluminum alloy containing Si. The brazing filler metal ingot may be made of an Al-Si alloy containing, for example, 4.0% by mass or more and 13.0% by mass or less of Si.
[0045] Furthermore, the Al-Si alloy constituting the brazing material ingot may contain, in addition to Si, Al and unavoidable impurities, one or more alloying elements selected from the group consisting of Mg, Li, Ca, Bi (bismuth), Na (sodium), Sr (strontium), Sb (antimony), Zn, Cu, Fe, Mn, Cr, Ti, Zr, Sn and In.
[0046] When a brazing sheet is to be obtained in which the brazing filler metal contains a metal element that is more easily oxidized than Al, the brazing filler metal ingot may be made of an Al-Si alloy containing 4.0% by mass or more and 13.0% by mass or less of Si, and further containing one or more of the metal elements: more than 0% by mass and 3.0% by mass or less of Mg, more than 0% by mass and 0.30% by mass or less of Li, and more than 0% by mass and 0.30% by mass or less of Ca. The chemical composition of the brazing filler metal in the brazing sheet is the same as that of the brazing filler metal ingot.
[0047] ·Si: 4.0 mass% or more and 13.0 mass% or less The Al-Si alloy constituting the brazing filler metal ingot contains 4.0% by mass or more and 13.0% by mass or less of Si. By setting the Si content in the brazing filler metal ingot within the above-mentioned specific range, brazing performance in flux-free brazing can be further improved. If the Si content in the brazing filler metal is less than 4.0% by mass, problems such as an insufficient amount of brazing filler metal or reduced fluidity of the brazing filler metal may occur, potentially resulting in poor brazing performance. If the Si content in the brazing filler metal exceeds 13.0% by mass, the amount of core metal melted during brazing heating may be excessively large. Furthermore, in this case, coarse primary Si crystals are likely to form in the brazing filler metal. After the brazing filler metal is melted, well-shaped molten holes may be easily formed, originating from the coarse primary Si crystals.
[0048] ·Mg: 0 mass% or more and 3.0 mass% or less, Li: 0 mass% or more and 0.30 mass% or less, Ca: 0 mass% or more and 0.30 mass% or less The Al-Si alloy constituting the brazing filler metal ingot may optionally contain one or more of the following metal elements: 3.0% by mass or less Mg, 0.30% by mass or less Li, and 0.30% by mass or less Ca. When the brazing filler metal ingot contains one or more of the following metal elements: more than 0% by mass and 3.0% by mass or less Mg, more than 0% by mass and 0.30% by mass or less Li, and more than 0% by mass and 0.30% by mass or less Ca, a brazing sheet can be obtained that includes a brazing filler metal containing these metal elements.
[0049] The metal elements mentioned above are more easily oxidized than Al, and therefore have the effect of destroying the oxide film present on the surface of the brazing sheet and the surface of the mating material during brazing. Therefore, by producing a brazing sheet using a brazing filler metal ingot containing these metal elements, a brazing sheet that allows flux-free brazing can be obtained.
[0050] The Mg content in the brazing filler metal ingot is preferably 0.10% by mass or more, and more preferably 0.20% by mass or more. In this case, the Mg in the brazing filler metal can sufficiently destroy the oxide films present on the surface of the brazing sheet and the surface of the mating material. As a result, brazing properties in flux-free brazing can be further improved. From the same perspective, the Li content in the brazing filler metal ingot is preferably 0.0010% by mass or more, and more preferably 0.0040% by mass or more. Furthermore, the Ca content in the brazing filler metal ingot is preferably 0.0010% by mass or more, and more preferably 0.0040% by mass or more.
[0051] Furthermore, when the Mg content of the brazing filler metal ingot is 0% by mass or more but less than 0.10% by mass, and the Li content and Ca content are each 0% by mass or more but less than 0.0010% by mass, it is preferable that the aluminum ingot adjacent to the brazing filler metal ingot be made of an aluminum material containing 0.20% by mass or more of Mg. Thus, even when the brazing filler metal ingot does not contain any of the metal elements described above or contains relatively small amounts of the metal elements described above, by increasing the content of metal elements that are more easily oxidized than Al contained in the layer of the brazing sheet adjacent to the brazing filler metal, i.e., the core material, intermediate material, etc., the amount of metal elements such as Mg that migrate from the core material, etc. to the brazing filler metal can be increased. As a result, the oxide film can be sufficiently destroyed during brazing.
[0052] On the other hand, if the content of Mg, Li, or Ca in the brazing filler ingot is excessively high, oxides of these metal elements are likely to form on the surface of the brazing sheet, which may lead to deterioration of brazability. By setting the Mg content in the brazing filler ingot to 3.0 mass% or less and the Li content and Ca content to 0.30 mass% or less, respectively, the amount of oxides of these metal elements formed on the surface of the brazing sheet can be reduced, and deterioration of brazability can be avoided. From the viewpoint of further reducing the amount of oxides of these metal elements formed on the surface of the brazing sheet, the Mg content in the brazing filler ingot is preferably 1.5 mass% or less. From the same viewpoint, the Li content in the brazing filler ingot is preferably 0.10 mass% or less. Furthermore, the Ca content in the brazing filler ingot is preferably 0.10 mass% or less.
[0053] ·Bi: 0 mass% or more and 1.0 mass% or less The Al-Si alloy constituting the brazing filler metal ingot may contain 1.0 mass% or less of Bi as an optional component. When the brazing filler metal ingot contains more than 0 mass% and 1.0 mass% or less of Bi, a brazing sheet with a brazing filler metal containing Bi can be obtained. Bi has the effect of reducing the surface tension of the brazing filler metal generated during brazing and improving brazing properties in flux-free brazing. From the viewpoint of further improving brazing properties in flux-free brazing, the Bi content in the brazing filler metal ingot is preferably 0.0040 mass% or more, and more preferably 0.010 mass% or more.
[0054] However, if the Bi content in the brazing filler metal ingot is excessively high, it becomes difficult to obtain the effect of improving brazeability commensurate with the Bi content. In addition, in this case, the brazing filler metal is likely to discolor after brazing, which may result in poor appearance. By setting the Bi content in the brazing filler metal ingot to 1.0 mass% or less, preferably 0.40 mass% or less, it is possible to avoid these problems and further improve brazeability.
[0055] ·Na: 0 mass% or more and 0.050 mass% or less, Sr: 0 mass% or more and 0.050 mass% or less, Sb: 0 mass% or more and 0.050 mass% or less, The Al-Si alloy constituting the brazing filler metal ingot may optionally contain one or more of the following elements: 0.050% by mass or less Na, 0.050% by mass or less Sr, and 0.050% by mass or less Sb. When the brazing filler metal ingot contains one or more of more than 0% by mass and 0.050% by mass or less Na, more than 0% by mass and 0.050% by mass or less Sr, and more than 0% by mass and 0.050% by mass or less Sb, a brazing sheet including a brazing filler metal containing these elements can be obtained.
[0056] Na, Sr, and Sb in the brazing filler metal all have the effect of refining Si particles in the brazing filler metal and improving the fluidity of the molten brazing filler metal. By producing a brazing sheet using a brazing filler metal ingot containing one or more elements selected from the group consisting of more than 0% by mass and not more than 0.050% by mass of Na, more than 0% by mass and not more than 0.050% by mass of Sr, and more than 0% by mass and not more than 0.050% by mass of Sb, the fluidity of the molten brazing filler metal can be increased, and brazability can be further improved.
[0057] ·Zn: 0 mass% or more and 8.0 mass% or less, Sn: 0 mass% or more and 0.10 mass% or less, In: 0 mass% or more and 0.10 mass% or less The Al-Si alloy constituting the brazing filler metal ingot may optionally contain one or more of the following elements: 8.0% by mass or less Zn, 0.10% by mass or less Sn, and 0.10% by mass or less In. When the brazing filler metal ingot contains one or more of more than 0% by mass and 8.0% by mass or less Zn, more than 0% by mass and 0.10% by mass or less Sn, and more than 0% by mass and 0.10% by mass or less In, a brazing sheet including a brazing filler metal containing these elements can be obtained.
[0058] Zn, Sn, and In in a brazing filler metal all have the effect of making the natural electrode potential of the brazing filler metal less noble. Making the natural electrode potential of the brazing filler metal less noble allows the brazing filler metal to function as a sacrificial anode in an aluminum product after brazing. However, if the content of Zn, Sn, or In in the brazing filler metal is excessively high, the natural electrode potential of the brazing filler metal may be excessively reduced, and the sacrificial corrosion protection effect may be prematurely impaired. By producing a brazing sheet using a brazing filler metal ingot containing one or more elements selected from the group consisting of more than 0% by mass and not more than 8.0% by mass of Zn, more than 0% by mass and not more than 0.10% by mass of Sn, and more than 0% by mass and not more than 0.10% by mass of In, the brazing filler metal can function as a sacrificial anode and the sacrificial corrosion protection effect of the brazing filler metal can be maintained for a longer period of time.
[0059] ·Cu: 0 mass% or more and 4.0 mass% or less The Al-Si alloy constituting the brazing filler metal ingot may contain 4.0 mass% or less of Cu as an optional component. When the brazing filler metal ingot contains more than 0 mass% and 4.0 mass% or less of Cu, a brazing sheet with a brazing filler metal containing Cu can be obtained. Cu in the brazing filler metal makes the natural electrode potential of the brazing filler metal more noble and lowers the melting point.
[0060] By producing a brazing sheet using a brazing filler metal ingot containing more than 0% by mass and not more than 4.0% by mass of Cu, the natural electrode potential of the brazing filler metal can be appropriately increased, and the corrosion resistance of the brazing filler metal can be improved. Furthermore, by setting the Cu content in the brazing filler metal in the specified range, the fluidity of the brazing filler metal can be increased, and brazability can be further improved.
[0061] ·Fe: 0 mass% or more and 1.0 mass% or less The Al-Si alloy constituting the brazing filler metal ingot may contain 1.0 mass% or less of Fe as an optional component. When the brazing filler metal ingot contains more than 0 mass% and 1.0 mass% or less of Fe, a brazing sheet with a brazing filler metal containing Fe can be obtained. The Fe in the brazing filler metal in the brazing sheet crystallizes relatively large Al-Fe intermetallic compounds in the brazing filler metal, which has the effect of refining the crystal grains of the brazing filler metal after brazing.
[0062] However, if the Fe content in the brazing filler metal ingot is excessively high, coarse Al-Fe intermetallic compounds are likely to form during casting, which may lead to a decrease in the formability of the brazing sheet. By producing a brazing sheet using a brazing filler metal ingot containing more than 0 mass% and not more than 1.0 mass% Fe, the above-mentioned effects can be achieved while avoiding a decrease in formability.
[0063] ·Mn: 0 mass% or more and 1.0 mass% or less, Cr: 0 mass% or more and 0.30 mass% or less, Ti: 0 mass% or more and 0.30 mass% or less, Zr: 0 mass% or more and 0.30 mass% or less The Al-Si alloy constituting the brazing filler metal ingot may optionally contain one or more of the following elements: 1.0% by mass or less Mn, 0.30% by mass or less Cr, 0.30% by mass or less Ti, and 0.30% by mass or less Zr. When the brazing filler metal ingot contains one or more of more than 0% by mass and 1.0% by mass or less Mn, more than 0% by mass and 0.30% by mass Cr, more than 0% by mass and 0.30% by mass Ti, and more than 0.30% by mass Zr, a brazing sheet including a brazing filler metal containing these elements can be obtained.
[0064] Mn, Cr, Ti, and Zr in the brazing filler metal precipitate fine intermetallic compounds in the brazing filler metal, coarsening the crystal grains of the brazing filler metal before brazing. By coarsening the crystal grains of the brazing filler metal before brazing, the number of crystal grain boundaries present in the brazing filler metal can be reduced. This reduces the amount of metal elements such as Mg that migrate from the interior of the core material, brazing filler metal, etc. through the crystal grain boundaries of the brazing filler metal to the surface of the brazing sheet. As a result, oxidation of metal elements such as Mg on the surface of the brazing filler metal can be suppressed, preventing deterioration of brazeability.
[0065] However, if the content of Mn, Cr, Ti, or Zr in the brazing filler metal ingot is excessively high, coarse intermetallic compounds are likely to form during casting, which may lead to a deterioration in the formability of the brazing sheet. By producing a brazing sheet using a brazing filler metal ingot containing one or more elements selected from the group consisting of more than 0% by mass and not more than 1.0% by mass of Mn, more than 0% by mass and not more than 0.30% by mass of Cr, more than 0% by mass and not more than 0.30% by mass of Ti, and more than 0% by mass and not more than 0.30% by mass of Zr, it is possible to improve the brazing performance while avoiding a deterioration in the formability of the brazing sheet.
[0066] From the viewpoint of obtaining the above-mentioned effects in a balanced manner, the aluminum material constituting the brazing filler metal ingot preferably has a chemical composition consisting of 4.0 to 13.0 mass% Si, 0.05 to 0.50 mass% Fe, 0.10 to 1.0 mass% Mg, and 0.0040 to 0.50 mass% Bi, with the balance being Al and unavoidable impurities, and more preferably has a chemical composition consisting of 6.0 to 12.0 mass% Si, 0.20 to 0.40 mass% Fe, 0.30 to 1.2 mass% Mg, and 0.050 to 0.35 mass% Bi, with the balance being Al and unavoidable impurities.
[0067] Furthermore, when attempting to obtain a brazing sheet that does not contain Mg in the brazing filler metal, it is preferable that the aluminum material constituting the brazing filler metal ingot has a chemical composition that contains Si: 6.0 mass% to 12.0 mass% inclusive, Fe: 0.20 mass% to 0.40 mass% inclusive, and Bi: 0.050 mass% to 0.35 mass% inclusive, with the remainder being Al and unavoidable impurities.
[0068] (intermediate material blocks) When preparing the clad ingot, an intermediate ingot can be placed between the core ingot and the brazing filler ingot, thereby obtaining a brazing sheet in which an intermediate ingot consisting of the intermediate ingot is provided between the core ingot and the brazing filler ingot. The aluminum material constituting the intermediate ingot has, for example, a chemical composition different from that of the core ingot and the brazing filler ingot. More specifically, the aluminum material constituting the intermediate ingot may have a chemical composition consisting of Al and unavoidable impurities. Furthermore, the aluminum material constituting the intermediate ingot may contain, in addition to Al and unavoidable impurities, one or more alloying elements selected from the group consisting of Fe, Si, Mg, Cu, Mn, Zn, Cr, Ti, Zr, Sn, and In.
[0069] When a brazing sheet containing a metal element that is more easily oxidized than Al is to be obtained, the ingot for intermediate material may be made of an aluminum material containing more than 0 mass% and not more than 6.0 mass% Mg. The chemical composition of the intermediate material is the same as that of the ingot for intermediate material.
[0070] ·Fe: 0 mass% or more and 1.5 mass% or less The aluminum material constituting the intermediate ingot may contain 1.5% by mass or less of Fe as an optional component. When the intermediate ingot contains more than 0% by mass and not more than 1.5% by mass of Fe, a brazing sheet can be obtained that includes an intermediate material containing Fe. The effects of Fe in the intermediate material are similar to those of Fe in the core material described above. In other words, by producing a brazing sheet using an intermediate ingot containing more than 0% by mass and not more than 1.5% by mass of Fe, the strength of the intermediate material can be further improved while avoiding deterioration in corrosion resistance and deterioration in formability of the brazing sheet.
[0071] ·Si: 0 mass% or more and 13.0 mass% or less The aluminum material constituting the intermediate ingot may contain 13.0% by mass or less of Si as an optional component. When the intermediate ingot contains more than 0% by mass and not more than 13.0% by mass of Si, a brazing sheet including an intermediate material containing Si can be obtained. When the Si content in the intermediate material is in the range of more than 0% by mass and not more than 1.5% by mass, the strength of the intermediate material can be further improved. Furthermore, when the Si content in the intermediate material is more than 1.5% by mass and not more than 13.0% by mass, the intermediate material can be melted during brazing heating. This allows a larger amount of brazing filler metal to be supplied to the joined parts, thereby improving brazing performance. On the other hand, when the Si content in the intermediate material exceeds 13.0% by mass, there is a risk that the amount of melted core material during brazing heating will be excessively large.
[0072] ·Mg: 0 mass% or more and 6.0 mass% or less The aluminum material constituting the intermediate ingot may contain 6.0% by mass or less of Mg as an optional component. When the intermediate ingot contains more than 0% by mass and 6.0% by mass or less of Mg, a brazing sheet with an intermediate material containing Mg can be obtained. The Mg in the intermediate material diffuses and migrates to the brazing filler metal due to heating during brazing. The Mg that migrates to the brazing filler metal then destroys the oxide film present on the surface of the brazing sheet and the surface of the mating material together with the Mg in the brazing filler metal, enabling flux-free brazing.
[0073] From the viewpoint of further improving brazing properties in flux-free brazing, it is preferable that the Mg content in the intermediate ingot is 0.40 mass% or more, which allows a larger amount of Mg to migrate from the intermediate to the brazing filler metal due to heating during brazing.
[0074] On the other hand, if the Mg content in the intermediate ingot is excessively high, a large amount of Mg is likely to reach the surface of the brazing sheet during brazing. If the Mg that reaches the surface of the brazing sheet is oxidized during brazing, this may lead to a deterioration in brazability. By setting the Mg content in the intermediate ingot to 6.0 mass% or less, the amount of Mg oxides that form during brazing can be further reduced, thereby preventing a deterioration in brazability.
[0075] ·Cu: 0 mass% or more and 2.0 mass% or less The aluminum material constituting the intermediate ingot may contain 2.0% by mass or less of Cu as an optional component. When the intermediate ingot contains more than 0% by mass and not more than 2.0% by mass of Cu, a brazing sheet can be obtained that includes an intermediate material containing Cu. The effects of Cu in the intermediate material are similar to those of Cu in the core material described above. That is, by producing a brazing sheet using an intermediate ingot containing more than 0% by mass and not more than 2.0% by mass of Cu, the strength and corrosion resistance of the intermediate material can be further improved while avoiding the occurrence of intergranular corrosion and deterioration of brazeability.
[0076] ·Mn: 0 mass% or more and 2.0 mass% or less The aluminum material constituting the intermediate ingot may contain 2.0% by mass or less of Mn as an optional component. When the intermediate ingot contains more than 0% by mass and not more than 2.0% by mass of Mn, a brazing sheet can be obtained that includes an intermediate material containing Mn. The effects of Mn in the intermediate material are similar to those of Mn in the core material described above. In other words, by producing a brazing sheet using an intermediate ingot containing more than 0% by mass and not more than 2.0% by mass of Mn, the strength and corrosion resistance of the intermediate material can be further improved while avoiding deterioration in the manufacturability of the brazing sheet.
[0077] ·Zn: 0 mass% or more and 6.5 mass% or less, Sn: 0 mass% or more and 0.10 mass% or less, In: 0 mass% or more and 0.10 mass% or less The aluminum material constituting the intermediate ingot may contain, as optional components, one or more of the following elements: 6.5% by mass or less Zn, 0.10% by mass or less Sn, and 0.10% by mass or less In. When the intermediate ingot contains one or more of the following elements: more than 0% by mass and 6.5% by mass or less Zn, more than 0% by mass and 0.10% by mass or less Sn, and more than 0% by mass and 0.10% by mass or less In, a brazing sheet can be obtained that includes an intermediate material containing these elements.
[0078] The effects of Zn, Sn, and In in the intermediate material are similar to those of the Zn, Sn, and In in the core material described above. That is, by producing a brazing sheet using an intermediate material ingot containing one or more elements selected from the group consisting of more than 0% by mass and up to 6.5% by mass of Zn, more than 0% by mass and up to 0.10% by mass of Sn, and more than 0% by mass and up to 0.10% by mass of In, the intermediate material can function as a sacrificial anode, and the sacrificial corrosion protection effect of the intermediate material can be maintained for a longer period of time.
[0079] ·Cr: 0 mass% or more and 0.30 mass% or less, Zr: 0 mass% or more and 0.30 mass% or less The aluminum material constituting the intermediate ingot may optionally contain one or two of 0.30% by mass or less of Cr and 0.30% by mass or less of Zr. When the intermediate ingot contains one or two of the elements Cr: more than 0% by mass and 0.30% by mass or less and Zr: more than 0% by mass and 0.30% by mass or less, a brazing sheet can be obtained that includes an intermediate material containing these elements.
[0080] The effects of Cr and Zr in the intermediate material are similar to those of Cr and Zr in the core material described above. That is, by producing a brazing sheet using an intermediate ingot containing one or two of more than 0% by mass and up to 0.30% by mass of Cr and more than 0% by mass and up to 0.30% by mass of Zr, it is possible to more effectively suppress the occurrence of erosion while avoiding deterioration in the manufacturability of the brazing sheet.
[0081] ·Ti: 0 mass% or more and 0.30 mass% or less The aluminum material constituting the intermediate ingot may contain up to 0.30% by mass of Ti as an optional component. When the intermediate ingot contains more than 0% by mass and up to 0.30% by mass of Ti, a brazing sheet can be obtained that includes an intermediate material containing Ti. The effects of Ti in the intermediate material are similar to those of Ti in the core material described above. That is, by producing a brazing sheet using an intermediate ingot containing more than 0% by mass and up to 0.30% by mass of Ti, it is possible to more effectively suppress the progression of corrosion in the depth direction of the intermediate material while avoiding deterioration of rolling ability and corrosion resistance.
[0082] From the viewpoint of obtaining a brazing sheet that includes an intermediate material that does not melt during brazing heating and that can achieve the above-mentioned effects in a balanced manner, the aluminum material that constitutes the intermediate material ingot should contain Fe: 0.05% by mass or more and 0.50% by mass or less, Si: 0.10% by mass or more and 0.50% by mass or less, Mg: 0.10% by mass or more and 3.0% by mass or less, Cu: 0.05% by mass or more and 0.50% by mass or less, Mn: 0.50% by mass or more and 1.5% by mass or less, and Ti: 0.01% by mass or more and 0.15% by mass or less. and the balance is a chemical composition consisting of Al and unavoidable impurities. It is preferable that the alloy contains Fe: 0.05% by mass to 0.30% by mass, Si: 0.15% by mass to 0.35% by mass, Mg: 0.50% by mass to 3.0% by mass, Cu: 0.10% by mass to 0.50% by mass, Mn: 1.0% by mass to 1.3% by mass, and Ti: 0.01% by mass to 0.15% by mass, with the balance being a chemical composition consisting of Al and unavoidable impurities.
[0083] Furthermore, when attempting to obtain a brazing sheet having an intermediate material that can melt during brazing heating, it is preferable that the aluminum material constituting the intermediate material ingot contains Fe: 0.20 mass% to 0.40 mass%, Si: 6.0 mass% to 12.0 mass%, Mg: 0.50 mass% to 3.0 mass%, Bi: 0 mass% to 0.35 mass%, with the remainder having a chemical composition consisting of Al and unavoidable impurities.
[0084] (lump for leather) When preparing the clad ingot, a brazing material ingot is placed on one side of a core ingot and a skin material ingot is placed on the other side, thereby obtaining a brazing sheet in which the brazing material is provided on one side of the core ingot and the skin material is provided on the other side. The chemical composition of the aluminum material constituting the skin material ingot may be appropriately determined depending on the function to be imparted by the skin material. For example, the aluminum material constituting the skin material ingot may have a chemical composition consisting of Al and unavoidable impurities. In this case, the purity of Al is preferably, for example, 99.9% by mass or more.
[0085] Furthermore, the aluminum material constituting the cladding ingot may contain, in addition to Al and inevitable impurities, one or more alloy elements selected from the group consisting of Fe, Si, Mg, Cu, Mn, Zn, Cr, Ti, Zr, Sn, and In. The chemical composition of the cladding material is the same as that of the cladding ingot.
[0086] ·Fe: 0 mass% or more and 1.5 mass% or less The aluminum material constituting the cladding ingot may contain 1.5% by mass or less of Fe as an optional component. When the cladding ingot contains more than 0% by mass and not more than 1.5% by mass of Fe, a brazing sheet with a cladding material containing Fe can be obtained. The effects of Fe in the cladding material are similar to those of Fe in the core material described above. That is, by producing a brazing sheet using a cladding ingot containing more than 0% by mass and not more than 1.5% by mass of Fe, it is possible to further improve the strength of the cladding material while avoiding deterioration in corrosion resistance and deterioration in formability of the brazing sheet.
[0087] ·Si: 0 mass% or more and 5.0 mass% or less The aluminum material constituting the cladding ingot may contain 5.0% by mass or less of Si as an optional component. When the cladding ingot contains more than 0% by mass and less than 5.0% by mass of Si, a brazing sheet with a cladding material containing Si can be obtained. The Si in the cladding has the effect of improving the strength of the cladding. However, if the Si content in the cladding is excessively high, the melting point of the cladding material will be excessively low, which may make the cladding material more susceptible to deformation during brazing. By producing a brazing sheet using a cladding ingot containing more than 0% by mass and less than 5.0% by mass of Si, it is possible to further improve the strength while avoiding deformation of the cladding material.
[0088] Furthermore, by setting the Si content in the cladding ingot to 1.5 mass% or more, the cladding material can be kept in a semi-molten state during brazing, which allows brazing to be performed on the surface of the brazing sheet facing the cladding material with the mating material.
[0089] ·Mg: 0 mass% or more and 3.0 mass% or less The aluminum material constituting the cladding ingot may contain 3.0 mass% or less of Mg as an optional component. When the cladding ingot contains more than 0 mass% and 3.0 mass% or less of Mg, a brazing sheet with a cladding material containing Mg can be obtained. The Mg in the cladding material has the effect of improving the strength of the cladding material.
[0090] However, if the Mg content in the cladding ingots is excessively high, cracks are more likely to occur in the cladding during the manufacturing process of the brazing sheet. By manufacturing a brazing sheet using a cladding ingot containing more than 0 mass% and 3.0 mass% or less of Mg, it is possible to further improve the strength of the cladding while avoiding deterioration in the manufacturability of the brazing sheet.
[0091] ·Cu: 0 mass% or more and 1.0 mass% or less The aluminum material constituting the cladding ingot may contain 1.0% by mass or less of Cu as an optional component. When the cladding ingot contains more than 0% by mass and less than or equal to 1.0% by mass of Cu, a brazing sheet with a cladding material containing Cu can be obtained. The effects of Cu in the cladding material are similar to those of Cu in the core material described above. That is, by producing a brazing sheet using a cladding ingot containing more than 0% by mass and less than or equal to 1.0% by mass of Cu, the strength and corrosion resistance of the cladding material can be further improved while avoiding the occurrence of intergranular corrosion and deterioration of brazeability.
[0092] ·Mn: 0 mass% or more and 2.0 mass% or less The aluminum material constituting the cladding ingot may contain 2.0 mass% or less of Mn as an optional component. When the cladding ingot contains more than 0 mass% and 2.0 mass% or less of Mn, a brazing sheet with a cladding material containing Mn can be obtained. Mn in the cladding material has the effect of improving the strength of the cladding material.
[0093] However, if the Mn content in the cladding ingots is excessively high, cracks are more likely to occur in the cladding during the manufacturing process of the brazing sheet. By producing a brazing sheet using a cladding ingot containing more than 0 mass% and 2.0 mass% or less of Mn, it is possible to further improve the strength of the cladding while avoiding deterioration in the manufacturability of the brazing sheet.
[0094] ·Zn: 0 mass% or more and 6.5 mass% or less, Sn: 0 mass% or more and 0.10 mass% or less, In: 0 mass% or more and 0.10 mass% or less The aluminum material constituting the cladding ingot may contain, as optional components, one or more of the following elements: 6.5% by mass or less Zn, 0.10% by mass or less Sn, and 0.10% by mass or less In. When the cladding ingot contains one or more of the following elements: more than 0% by mass and 6.5% by mass or less Zn, more than 0% by mass and 0.10% by mass or less Sn, and more than 0% by mass and 0.10% by mass or less In, a brazing sheet with a cladding containing these elements can be obtained.
[0095] The effects of Zn, Sn, and In in the cladding material are similar to those of Zn, Sn, and In in the core material described above. That is, by producing a brazing sheet using cladding ingots containing one or more elements selected from the group consisting of more than 0% by mass and up to 6.5% by mass of Zn, more than 0% by mass and up to 0.10% by mass of Sn, and more than 0% by mass and up to 0.10% by mass of In, the cladding material can function as a sacrificial anode, and the sacrificial corrosion protection effect of the cladding material can be maintained for a longer period of time.
[0096] ·Cr: 0 mass% or more and 0.30 mass% or less, Ti: 0 mass% or more and 0.30 mass% or less, Zr: 0 mass% or more and 0.30 mass% or less The aluminum material constituting the cladding ingot may optionally contain one or more of the following elements: 0.30% by mass or less Cr, 0.30% by mass or less Ti, and 0.30% by mass or less Zr. When the cladding ingot contains one or two of the following elements: more than 0% by mass and less than 0.30% by mass Cr, more than 0% by mass and less than 0.30% by mass Ti, and more than 0% by mass and less than 0.30% by mass Zr, a brazing sheet can be obtained with a cladding material containing these elements. The Cr, Ti, and Zr in the cladding material have the effect of improving the strength of the cladding material.
[0097] However, if the content of Cr, Ti, or Zr in the cladding ingot is excessively high, coarse intermetallic compounds are likely to form during casting, which may lead to a deterioration in the formability of the brazing sheet. By producing a brazing sheet using a cladding ingot containing one or two elements from among more than 0% by mass and not more than 0.30% by mass of Cr, more than 0% by mass and not more than 0.30% by mass of Ti, and more than 0% by mass and not more than 0.30% by mass of Zr, it is possible to further improve the strength of the cladding while avoiding a deterioration in the formability of the brazing sheet.
[0098] From the viewpoint of obtaining a balanced combination of the above-mentioned effects, it is preferable that the aluminum material constituting the cladding ingot contains Fe: 0.05% by mass to 0.50% by mass, Si: 0.10% by mass to 0.50% by mass, Mg: 0.10% by mass to 1.0% by mass, Cu: 0.05% by mass to 0.50% by mass, Mn: 0.50% by mass to 1.5% by mass, and Ti: 0.01% by mass to 0.15% by mass, with the remainder being Al and unavoidable impurities.
[0099] Furthermore, when attempting to obtain a brazing sheet that does not contain Mg in the cladding material, it is preferable that the aluminum material that constitutes the cladding material ingot has a chemical composition that contains Fe: 0.05% by mass to 0.50% by mass, Si: 0.05% by mass to 0.20% by mass, and Zn: 1.0% by mass to 4.0% by mass, with the remainder being Al and unavoidable impurities.
[0100] <Hot rolling process> In the method for manufacturing the brazing sheet, a hot rolling step is carried out after the lamination step. In the hot rolling step, the clad ingot obtained in the lamination step is hot rolled. This allows a clad plate to be obtained in which adjacent aluminum ingots are bonded together. The rolling conditions in the hot rolling step may be set appropriately depending on the configuration of the clad ingot and the configuration of the brazing sheet to be finally obtained. Furthermore, after the hot rolling step, the clad plate may be heated and subjected to a homogenization treatment as needed.
[0101] <Cold rolling process> After the hot rolling step, the obtained clad plate is subjected to a cold rolling step in which the clad plate is subjected to one or more passes of cold rolling. By cold rolling the clad plate, the thickness of the clad plate is reduced to the desired thickness of the brazing sheet. The number of passes and rolling conditions in the cold rolling step may be appropriately set depending on the configuration of the clad plate and the desired configuration of the brazing sheet. Furthermore, the clad plate may be heated and annealed as needed before, during, or after cold rolling.
[0102] <Etching process> On the surface of the brazing sheet obtained by cold rolling, there is an oxide film formed when the clad plate or brazing sheet is heated to a high temperature during the hot rolling or heat treatment described above. In order to weaken this oxide film, in the etching process, the surface of the brazing sheet is treated with NaOH at a concentration of 0.05 mass % or more and 1.0 mass % or less. The concentration of KOH is 0.10 mass % or more and 1.0 mass % or less. Etching is carried out using an alkaline etching solution.
[0103] More specifically, in the etching step, the specific alkaline etching solution is brought into contact with the surface of the brazing sheet to remove the oxide film present on the surface of the brazing material, and then the brazing sheet is washed to remove the alkaline etching solution.The brazing sheet is then dried to remove the cleaning solution used to clean the brazing sheet.Water or the like is used as the cleaning solution.
[0104] In the etching step, the time for which the brazing sheet is in contact with the alkaline etching solution can be appropriately set within a range of, for example, 5 to 120 seconds, and the temperature of the alkaline etching solution in the etching step can be appropriately set within a range of, for example, 20 to 80°C.
[0105] The etching step may be performed between passes of cold rolling in the cold rolling step, or may be performed after the cold rolling step is completed. When the etching step is performed after the cold rolling step is completed, etching may be performed in the state of a coil material before cutting to a desired size, or etching may be performed after processing for forming the brazing sheet into a desired shape, such as cutting or pressing.
[0106] The alkaline etching solution used in the etching step is an aqueous solution with an NaOH concentration of 0.05% by mass or more and 1.0% by mass or less. By setting the NaOH concentration in the alkaline etching solution to the specific range, a brazing sheet with excellent brazing properties can be easily obtained. The reason why the specific alkaline etching solution can improve brazing properties in flux-free brazing is not necessarily clear at this time, but it is thought that the brazing properties in flux-free brazing are improved, for example, by the following mechanism.
[0107] As described above, a strong oxide film formed during hot rolling or the like exists on the outermost surface of the brazing filler metal before the etching process. Furthermore, an Al matrix and Si particles dispersed in the Al matrix exist inside the oxide film. When an alkaline etching solution is brought into contact with the surface of the brazing filler metal, the Al matrix is selectively dissolved by the alkaline etching solution that penetrates into the oxide film through defects in the oxide film.
[0108] As the dissolution of the Al matrix progresses inside the oxide film, a gap forms between the Al matrix and the oxide film. When this gap becomes large enough, the oxide film peels off from the Al matrix. As a result, it is presumed that the strong oxide film formed during hot rolling or other processes can be removed from the surface of the brazing filler metal.
[0109] After the tough oxide film is removed, a fresh surface of the brazing filler metal is exposed on the surface. If etching is terminated in this state and the brazing sheet is washed and dried, the fresh surface of the brazing filler metal will be oxidized by the atmosphere. The oxide film formed on the surface of the brazing filler metal in this way is more fragile than the oxide film formed during hot rolling or the like, and is therefore easily destroyed by metal elements such as Mg in the brazing sheet. Therefore, it is presumed that etching using the specific alkaline etching solution can produce a brazing sheet with excellent brazing properties for flux-free brazing.
[0110] If the NaOH concentration in the alkaline etching solution is lower than the above-mentioned specific range, the removal of the tough oxide film in the etching step is likely to be insufficient, which may result in deterioration of brazability.
[0111] Furthermore, if the NaOH concentration in the alkaline etching solution is higher than the specific range, the brazing property may be deteriorated. The reasons for this are considered to be, for example, as follows: When the NaOH concentration in the alkaline etching solution is high, the dissolution of the Al matrix proceeds rapidly during the etching process. However, the Si particles in the brazing filler metal are not dissolved by the alkaline etching solution. Therefore, if the dissolution of the Al matrix proceeds rapidly, the Si particles in the Al matrix are exposed, or the Si particles fall off as the Al matrix around the Si particles dissolves, which can easily result in the formation of irregularities on the surface of the brazing filler metal.
[0112] Therefore, it is presumed that excessive etching by an alkaline etching solution with a high NaOH concentration increases the surface irregularities of the brazing filler metal, and the true surface area of the brazing filler metal, i.e., the surface area of the brazing filler metal taking into account the surface irregularities, increases. Furthermore, it is presumed that if a brazing filler metal with large irregularities is exposed to the atmosphere, the true surface area of the oxide film formed on the brazing filler metal surface also increases. Therefore, when flux-free brazing is performed using such a brazing sheet, it is presumed that the destruction of the oxide film by metal elements such as Mg is likely to be insufficient, which may lead to deterioration of brazability.
[0113] From the viewpoint of further improving the brazing properties of the brazing sheet, the NaOH concentration in the alkaline etching liquid is preferably 0.05 mass % or more and 0.50 mass % or less, and more preferably 0.05 mass % or more and 0.30 mass % or less.
[0114] In addition to NaOH, KOH is dissolved in the alkaline etching solution. There are The concentration of KOH in the alkaline etching solution is preferably 0.10 mass % or more and 1.0 mass % or less. In this case, the brazing property of the finally obtained brazing sheet can be further improved. Furthermore, by setting the concentration of KOH in the alkaline etching solution within the above-mentioned specific range, deterioration of the alkaline etching solution can be suppressed and the life of the alkaline etching solution can be extended.
[0115] From the viewpoint of further enhancing this effect, the KOH concentration in the alkaline etching solution is preferably 0.10% by mass to 0.70% by mass, and more preferably 0.10% by mass to 0.50% by mass. From the same viewpoint, the NaOH concentration in the alkaline etching solution is preferably 0.05% by mass to 0.50% by mass and the KOH concentration is preferably 0.10% by mass to 0.70% by mass, and more preferably 0.05% by mass to 0.30% by mass and the KOH concentration is 0.10% by mass to 0.50% by mass.
[0116] It is preferable that the alkaline etching solution further contains a surfactant, which further shortens the time required for etching, suppresses unevenness in the reaction, and allows the entire brazing sheet to be etched uniformly.
[0117] <Smut removal process> The method for manufacturing a brazing sheet may include, after the etching step, a desmutting step of removing smut generated on the surface of the clad sheet in the etching step using a desmutting solution containing at least one of sulfuric acid and nitric acid. The desmutting solution used in the desmutting step is specifically an aqueous solution containing at least one of sulfuric acid and nitric acid.
[0118] In the desmutting process, a desmutting liquid is brought into contact with the surface of the brazing sheet to remove smut adhering to the surface of the brazing material, and then the brazing sheet is washed to remove the desmutting liquid.The brazing sheet is then dried to remove the cleaning liquid used to clean the brazing sheet.Water or the like is used as the cleaning liquid.
[0119] In the etching process, smut containing alloy elements contained in the brazing filler metal may adhere to the surface of the brazing filler metal. If smut adheres to the surface of the brazing filler metal, the brazing filler metal may become less wettable during brazing, which may lead to deterioration of brazing properties.
[0120] On the other hand, smut is easily dissolved in acids such as sulfuric acid and nitric acid. Therefore, by performing a smut removal step after the etching step, smut adhering to the surface of the brazing filler metal can be removed, and brazability can be further improved.
[0121] In the desmutting step, the time for which the brazing sheet is brought into contact with the desmutting liquid can be appropriately set within the range of, for example, 2 seconds or more and 60 seconds or less.
[0122] The brazing sheet obtained by the above-described manufacturing method can be used for flux-free brazing, i.e., brazing performed in an inert gas atmosphere without applying flux, such as nitrogen, argon, or helium.
[0123] In flux-free brazing, excessively high oxygen concentrations and dew points in an inert gas atmosphere can lead to deterioration of brazability. However, as described above, the brazing sheet has a weakened oxide film on the surface of the brazing material, so deterioration of brazability can be avoided even at relatively high oxygen concentrations and dew points. The brazing sheet can be used for flux-free brazing in an inert gas atmosphere with an oxygen concentration of 100 volume ppm or less and a dew point of −30° C. or less.
[0124] Although the heating conditions for flux-free brazing are not particularly limited, if the time required from the start of brazing heating until the brazing filler metal melts is excessively long, oxidation of the surface of the brazing filler metal may progress, resulting in a deterioration in brazing properties. From the viewpoint of avoiding such problems, brazing is preferably performed under heating conditions such that the time required from the time the temperature of the brazing sheet reaches 300°C until the time it reaches the solidus temperature of the brazing filler metal is 40 minutes or less. [Example]
[0125] Examples of the method for manufacturing the brazing sheet are described below. Note that the method for manufacturing the brazing sheet according to the present invention is not limited to the examples shown below, and the configuration can be changed as appropriate within the scope of the invention.
[0126] Example 1 This example describes a method for manufacturing a single-sided brazing sheet in which a brazing filler metal is laminated on one side of a core material. First, a core ingot is prepared. The ingot is made of an aluminum material containing 0.30% by mass of Si, 0.10% by mass of Fe, 0.12% by mass of Cu, 1.2% by mass of Mn, 0.60% by mass of Mg, and 0.10% by mass of Ti, with the remainder being Al and unavoidable impurities. Separately from the core ingot, a brazing filler metal ingot is prepared. The ingot is made of an Al-Si alloy containing 11.8% by mass of Si, 0.30% by mass of Fe, 0.60% by mass of Mg, and 0.30% by mass of Bi, with the remainder being Al and unavoidable impurities. A brazing filler metal ingot is then stacked on one side of the prepared core ingot to produce a two-layer clad ingot (lamination process).
[0127] Next, the clad ingot is hot-rolled to produce a clad plate in which the brazing filler metal is laminated on one side of the core material (hot-rolling process). This clad plate is subjected to one or more passes of cold rolling, and then final annealing is performed to reduce the thickness of the clad plate to 0.8 mm (cold-rolling process). Note that the clad ratio of the brazing filler metal in the clad plate after cold rolling, i.e., the ratio of the brazing filler metal thickness to the clad plate thickness, is 8%.
[0128] After cold rolling, the clad plate is degreased and washed to remove rolling oil from the surface of the clad plate. Next, the clad plate is brought into contact with an alkaline etching solution having an NaOH concentration shown in Table 1 to etch the surface of the clad plate. The temperature and treatment time of the alkaline etching solution brought into contact with the clad plate are as shown in Table 1. After etching is complete, the brazing sheet is washed with water to remove the alkaline etching solution, and then the brazing sheet is dried (etching step). Through the above steps, test materials A1 to A5 shown in Table 1 can be obtained.
[0129] Furthermore, for test materials A6 to A8 shown in Table 1, the brazing sheet after the etching step is brought into contact with a desmutting liquid having the composition shown in Table 1 to remove smut adhering to the surface of the brazing sheet. The treatment time for bringing the brazing sheet into contact with the desmutting liquid is as shown in Table 1. After smut removal is complete, the brazing sheet is washed with water to remove the desmutting liquid, and then the brazing sheet is dried (smut removal step).
[0130] Test material A9 shown in Table 1 is a test material for comparison with test materials A1 to A8. The method for producing test material A9 is the same as the method for producing test materials A1 to A5, except that the etching step is not performed after degreasing and cleaning.
[0131] The brazeability of test materials A1 to A9 can be evaluated by a gap filling test. In the gap filling test, first, test specimen 1 shown in FIG. 1 is assembled. As shown in FIG. 1, test specimen 1 has a horizontal plate 2 made of test materials A1 to A9 and a vertical plate 3 made of JIS A3003 alloy and having a thickness of 1.0 mm. Horizontal plate 2 is horizontally arranged with brazing filler metal 21 facing upward and core metal 22 facing downward. Vertical plate 3 is arranged perpendicular to horizontal plate 2. One longitudinal end 31 of vertical plate 3 abuts against brazing filler metal 21 of horizontal plate 2. Horizontal plate 2 has a width of 25 mm and a length of 60 mm. Vertical plate 3 has a width of 25 mm and a length of 55 mm.
[0132] A spacer 4 is interposed between the other longitudinal end 32 of the vertical plate 3 and the horizontal plate 2. This forms a gap S between the horizontal plate 2 and the vertical plate 3 that gradually widens from one end 31 of the vertical plate 3 toward the spacer 4. The spacer 4 is specifically a stainless steel round wire with a diameter of 1.6 mm, and is positioned 55 mm horizontally from the position where the vertical plate 3 abuts against the horizontal plate 2 (i.e., one end 31 of the vertical plate 3).
[0133] The test specimens are brazed using a nitrogen gas furnace. Specifically, the atmosphere inside the furnace is first set to a nitrogen gas atmosphere with an oxygen concentration of 10 ppm by volume or less, and the test specimens are placed inside the furnace with the temperature inside the furnace at 100°C or less. The test specimens are left in the furnace for 10 minutes, and then brazing heating begins. The brazing heating is performed by raising the temperature of the test specimens to 600°C and then holding the temperature at 600°C for 3 minutes. After brazing heating is completed, the test specimens are slowly cooled in the furnace until the temperature drops to a certain level, and then the test specimens are removed from the furnace.
[0134] In the gap filling test, brazeability can be evaluated based on the length L and shape of the fillet F formed after brazing (see Figure 1). In the "Brazeability" column of Table 1, the following criteria are entered: "A" if the length L of the fillet F exceeds 40 mm; "B" if the length L of the fillet F is 30 mm or more and 40 mm or less; "C" if the length L of the fillet F is less than 30 mm and there is little variation in the size of the fillet; and "D" if the length L of the fillet F is less than 30 mm and there is a large variation in the size of the fillet.
[0135] In the evaluation of brazing properties, cases marked "A" and "B" where the length L of the fillet F was 30 mm or more, and cases marked "C" where the variation in the size of the fillet F was small, were judged to have good brazing properties, while cases marked "D" where the length L of the fillet F was less than 30 mm and the variation in the size of the fillet F was large were judged to be unacceptable due to the risk of poor brazing.
[0136] [Table 1]
[0137] As shown in Table 1, alkaline etching solutions with NaOH concentrations within the specific range were used in the etching process for test materials A1 to A3 and test materials A6 to A8. Therefore, these test materials can have a longer fillet length L than test materials A4 and A5, which have NaOH concentrations outside the specific range, and test material A9, which was not subjected to the etching process.
[0138] Example 2 In this example, a method for manufacturing a double-sided brazing sheet in which brazing filler metal is laminated on both sides of a core material is described. In this example, first, a core ingot and two brazing filler metal ingots are prepared. The chemical compositions of the core ingot and the brazing filler metal ingots are the same as in Example 1. Next, a brazing filler metal ingot is laminated on both sides of the core ingot to produce a clad ingot with a three-layer structure (lamination process).
[0139] Next, the clad ingot is hot-rolled to produce a clad plate in which the brazing filler metal is laminated on both sides of the core material (hot-rolling process). This clad plate is subjected to one or more passes of cold rolling, and then final annealing is performed to reduce the thickness of the clad plate to 1.0 mm (cold-rolling process). Note that the clad ratio of the brazing filler metal in the clad plate after cold rolling, i.e., the ratio of the brazing filler metal thickness to the clad plate thickness, is 5%.
[0140] Thereafter, the degreasing and cleaning, etching and smut removal steps are carried out in the same order as in Example 1, thereby obtaining test materials B1 to B9 shown in Table 2. The composition, temperature and treatment time of the alkaline etching solution brought into contact with the clad plate in the etching step of this example are shown in Table 2. The composition of the desmutting solution brought into contact with the brazing sheet in the smut removal step of this example and the treatment time for contact with the desmutting solution are also shown in Table 2.
[0141] The brazeability of test materials B1 to B9 can be evaluated by a gap filling test in the same manner as in Example 1. Table 2 shows the evaluation results of the brazeability of test specimens using each test material.
[0142] [Table 2]
[0143] As shown in Table 2, an alkaline etching solution with an NaOH concentration within the specified range was used in the etching process for test materials B1 to B9. Therefore, these test materials have excellent brazability. Furthermore, a comparison of test materials B1 to B9 with test materials A6 to A8 shown in Table 1 reveals that the brazability of the brazing sheet can be further improved by using an aqueous solution in which both NaOH and KOH are dissolved as the alkaline etching solution. [Explanation of symbols]
[0144] 1 Test specimen 2 horizontal plate 21 Brazing filler metal 22 Heartwood 3 vertical plates 4 spacers F Fillet L Fillet length
Claims
1. A method for manufacturing a brazing sheet for brazing aluminum materials in an inert gas atmosphere without using a flux, comprising: a lamination process for producing a clad ingot by laminating a plurality of aluminum ingots including a core ingot made of an aluminum material and a brazing material ingot made of an Al-Si alloy and disposed on at least one side of the core ingot, wherein at least one of the core ingots, the brazing material ingot, and the aluminum ingots disposed between the core ingot and the brazing material ingot, contains a metal element that is more easily oxidized than Al; a hot rolling process for producing a clad plate including a core material made of the core material ingot and a brazing material made of the brazing material ingot and disposed on at least one surface of the core material ingot by hot rolling the clad ingot; A cold rolling step of subjecting the clad plate to one or more passes of cold rolling; and an etching step of etching the surface of the clad plate using an alkaline etching solution having a NaOH concentration of 0.05 mass% or more and 1.0 mass% or less and a KOH concentration of 0.10 mass% or more and 1.0 mass% or less between passes of cold rolling in the cold rolling step or after completion of the cold rolling step.
2. A method for manufacturing a brazing sheet as described in claim 1, wherein the concentration of NaOH in the alkaline etching solution is 0.10 mass% or more and 0.50 mass% or less.
3. The method for manufacturing a brazing sheet according to claim 1 or 2, further comprising a desmutting step of removing smut generated on the surface of the clad plate in the etching step using a desmutting solution containing at least one of sulfuric acid and nitric acid after the etching step.
4. The Al-Si alloy constituting the brazing filler metal mass includes Si: 4.0% by mass or more and 13.0% by mass, Mg: 0% by mass or more and 3.0% by mass or less, Li: 0% by mass or more and 0.30% by mass or less, Ca: 0% by mass or more and 0.30% by mass or less, Bi: 0 quality. % to 1.0 mass%, Na: 0 to 0.050 mass%, Sr: 0 to 0.050 mass%, Sb: 0 to 0.050 mass%, Zn: 0 to 8.0 mass%, Cu: 0 to 0 mass%4.
4. The method for producing a brazing sheet according to claim 1, wherein the brazing sheet has a chemical component consisting of Al and unavoidable impurities, Fe: 0 mass% or more and 1.0 mass% or less, Mn: 0 mass% or more and 1.0 mass% or less, Cr: 0 mass% or more and 0.30 mass% or less, Ti: 0 mass% or more and 0.30 mass% or less, Zr: 0 mass% or more and 0.30 mass% or less, Sn: 0 mass% or more and 0.10 mass% or less, and In: 0 mass% or more and 0.10 mass% or less.
5. 5. The method for producing a brazing sheet according to claim 1, wherein the aluminum material constituting the core ingot contains Fe: 0% by mass to 1.5% by mass, Si: 0% by mass to 1.5% by mass, Mg: 0% by mass to 3.0% by mass, Cu: 0% by mass to 2.0% by mass, Mn: 0% by mass to 2.0% by mass, Zn: 0% by mass to 6.5% by mass, Cr: 0% by mass to 0.30% by mass, Ti: 0% by mass to 0.30% by mass, Zr: 0% by mass to 0.30% by mass, Sn: 0% by mass to 0.10% by mass, and In: 0% by mass to 0.10% by mass, with the remainder being chemical components consisting of Al and unavoidable impurities.
6. The clad ingot has the core ingot, the brazing material ingot arranged on one surface of the core ingot, and a skin material ingot made of aluminum material arranged on the other surface of the core ingot, and the aluminum material constituting the skin material ingot has Fe: 0 mass% or more and 1.5 mass% or less, Si: 0 mass% or more and 5.0 mass% or less, Mg: 0 mass% or more and 3.0 mass% or less, Cu: 0 mass% or more and 1.0 mass% or less, Mn: 0 mass% or more and 6. The method for producing a brazing sheet according to claim 1, wherein the brazing sheet has a chemical composition comprising: Zn: 0 mass% or more and 6.5 mass% or less; Cr: 0 mass% or more and 0.30 mass% or less; Ti: 0 mass% or more and 0.30 mass% or less; Zr: 0 mass% or more and 0.30 mass% or less; Sn: 0 mass% or more and 0.10 mass% or less; and In: 0 mass% or more and 0.10 mass% or less, with the balance being Al and unavoidable impurities.
Citation Information
Patent Citations
Production of brazing sheet for vacuum brazing
JP1992100696A
Aluminum alloy brazing sheet, its production and aluminum alloy heat exchanger
JP2001105174A
Brazing sheet for flux-less brazing
JP2014155955A
Aluminum alloy brazing sheet and production method thereof
JP2015030861A
Aluminum composite material for fluxless brazing
JP2015526290A